JUDICIAL FACTOR’S PARTICIPATION IN PRELIMINARY PROCEEDINGS – A COMPARATIVE PERSPECTIVE - Bojanowski, Tomasz (International Journal of Legal and Social Order, 2025)
The subject of the article is the analysis of the role of the judicial element in preparatory proceedings. The author presents the issue of the preparatory proceedings model, addressing historical and comparative aspects. Subsequently, the article discusses various configurations of the judicial element in preparatory proceedings, namely the model with an investigative judge, the model with a judge for preparatory proceedings, and the model involving court participation. The advantages and disadvantages of these models are highlighted, along with examples from selected countries. In conclusion, the author provides a summative evaluation, identifying what they consider the optimal model and procedural solution, and emphasizes the need for a reassessment of current practices.